Si-DIFA: Inovasi Digital untuk Meningkatkan Layanan Psoyandu Disabilitas dan Pemberdayaan Sosial Masyarakat di Kota Malang - May Lia Elfina; Susanti Prasetyaningrum; Zamah Sari; Muhammad Hisyam Kamil; Krisna Bimantoro (Yayasan Literasi Sains Indonesia, 2025)
Lingkar Sosial Indonesia, as a partner in this social service program, is a non-profit organization partner working on disability empowerment. The partner's main problem is the manual and illogical recording of data on Individuals with Special Needs (ISN) at the Disability Posyandu, which causes data to be easily lost and difficult to use for further planning programs. Posyandu activities have not been systematically structured, cadres' knowledge of promotive and preventive programs is limited, and socialization of job vacancies for people with disabilities is less than optimal. This program aims to develop technology-based solutions through the creation of a Disability Information System (Si-DIFA) that supports ISN data management, posyandu program development, educational information provision, and access to job vacancies specifically for people with disabilities. Program implementation includes five stages: (1) socialization and communication of needs, (2) training and application planning with technology experts, (3) creation and implementation of the Si-DIFA website, (4) mentoring and evaluation of cadre skills, and (5) continued planning through documentation and socialization. The results of the activity include the creation of a website-based application, namely, Si-DIFA, with features for ISN data collection, posyandu schedules, educational information, job vacancies, and statistical reports. A user manual has also been developed, tested with cadres, and socialization of its use has been conducted. This program has resulted in improved cadre skills, simplified recording and reporting, and expanded access to education for the community. Si-DIFA provides a strong managerial foundation for integrated health posts (Posyandu) for people with disabilities and has the potential to be replicated in other regions. The program has high potential for replication at other Posyandu for people with disabilities.